Pengaruh Model Kooperatif Tipe Make A Match Terhadap Hasil Belajar Siswa Dalam Pembelajaran IPS Kelas V SDN - Putri, Eliza; Indrawati, Tin; Hamimah, Hamimah (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2018)
This study aims to determine the effect of the cooperative model type make a match on student learning outcomes in social studies learning in class V SDN in Cluster I sub-district V Koto Kampung Dalam Padang Pariaman. This type of research is an experiment with true experiment design with the form of pretest-posttest control group. The sample of this study was class V SD 05 Subdistrict V Koto Kampung Dalam and class V SD 25 Subdistrict V Koto Kampung Dalam Padang Pariaman which was selected based on random cluster techniques. The results showed that there was an effect of the cooperative model type make a match on student learning outcomes in social studies learning with a value of tcount (4.9045)> t table (1.697). Keywords: cooperative model types Make A Match, IPS, the results of the study